2009
DOI: 10.1159/000230587
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Elderly Patients with Hip Fractures: A Two-Year Prospective Study of 1,944 Patients

Abstract: Background: Hip fracture patients are reported to have an increased mortality rate compared to the general population. In order to be able to reduce the morbidity and mortality after a hip fracture, our efforts to identify the patients at risk already upon admission to the hospital need to be increased. For such a risk assessment, robust, validated, and reproducible criteria are mandatory. Objective: To determine preoperative factors associated with mortality and to evaluate the combined use of the American So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
67
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 47 publications
15
67
1
3
Order By: Relevance
“…Elderly patients who died at 1 or 2 years after femoral neck fracture had a higher modified frailty index when compared with those who lived. Our results support the association of mortality and frailty demonstrated by other studies in multiple settings [12,13,21]. The modified frailty index appears to be a useful tool to predict mortality at 1 and 2 years status postfemoral neck fracture.…”
Section: Discussionsupporting
confidence: 90%
“…Elderly patients who died at 1 or 2 years after femoral neck fracture had a higher modified frailty index when compared with those who lived. Our results support the association of mortality and frailty demonstrated by other studies in multiple settings [12,13,21]. The modified frailty index appears to be a useful tool to predict mortality at 1 and 2 years status postfemoral neck fracture.…”
Section: Discussionsupporting
confidence: 90%
“…No studies were identified from Africa and only a few included from South East Asia or South America. We did not attempt to analyse findings by gender, although most studies included more than three quarters women and it is known that mortality rates are higher for men than women [45,56,57]. Pooling of study outcomes was not performed due to the wide variation in the type and reporting of outcomes used.…”
Section: Discussionmentioning
confidence: 99%
“…Certain variables were collected as measures of preoperative medical status, including the American Society of Anesthesiologists Physical Status (ASA PS) grade (1-6) [35], preoperative hemoglobin, cigarette smoking status, and body mass index (BMI), including those patients meeting obesity criteria (BMI C 30 kg/m 2 ). The ASA PS classification system is used to assess the fitness of a patient for surgery before beginning anesthesia and consists of six categories (PS 1: normal, healthy patient; PS 2: patient with mild, systemic disease; PS 3: patient with severe, systemic disease; PS 4: patient with severe, systemic disease that is a constant threat to life; PS 5: moribund patient who is not expected to survive without the operation; PS 6: brain-dead patient whose organs are being removed for donor purposes) [35].…”
Section: Methodsmentioning
confidence: 99%